Leadership Psychology: How Effective Leaders Manage Emotions in Organizations - Mohammad Bilutfikal Khofi (Research Psychologie, Orientation et Conseil, 2024)
This research explores how effective leaders manage their emotions in organizations, focusing on practical strategies that can be used in real-life situations. This research will use a literature review approach. The literature used in this research will be taken from various credible academic sources, including scholarly journals, books, and articles from Google Scholar. Keywords such as "leadership psychology," "emotional intelligence," "emotion management," "emotion management in leadership," and "leadership in crises" will be used in the literature collection. Researchers will use literature published within the last 10-15 years to ensure relevance to the modern context, although relevant classic research will also be considered. The literature collected will be selected based on the following main criteria: relevance, credibility, and timeliness. Data analysis using the Miles and Huberman model includes data reduction, presentation, and conclusion. The results of this research found that there are several main strategies that leaders can use to manage their emotions in organizations, namely: mindfulness, self-regulation, use of humor, and reframing. Each of these strategies plays an important role in helping leaders manage emotions positively and constructively.